﻿Vaccinium usneoides (Ericaceae), a new species from Yunnan, China - Yong-Jie Guo; Ting Zhang; Ji-Dong Ya; Wei Zhang; Xiu-Ying Shen; Zhou-Dong Han; Jing-Bo Ni; Jian-Yong Su; Yi-Hua Tong (PhytoKeys, 2023)
Vaccinium usneoides (Ericaceae), a new species from Fugong County of Yunnan Province, China is described and illustrated. This new species belongs to Vaccinium sect. Calcicolus and is most similar to V. brachyandrum, but differs in its branches hanging down, much smaller leaf blades, shorter inflorescences and pedicels, non-glandular tomentellate or densely pubescent inflorescence rachis and pedicels, densely white-pubescent hypanthium and pilose filaments.